Application of the Halal Guarantee System to Broilers in Traditional Markets: Worker’s Knowledge of Halal Guarantee - Handayani, Nur Atikah; Nahariah, Nahariah; Asnawi, Aslina; Hikmah, Hikmah (Hasanuddin Journal of Animal Science (HAJAS), 2023)
The Indonesian government's efforts to support food and beverage products that must be halal-certified by 2024 are by implementing a halal product guarantee system in the industry. One of the industries that must implement halal guarantees is poultry slaughterhouses. One of the criteria for a halal assurance system in a poultry slaughterhouse is the role of human resources.  This study aims to analyze the knowledge of human resources in Poultry Slaughterhouses. Application of knowledge about commitment and responsibility consists of halal criteria, human resource development, top management responsibilities, and training of halal staff. The object of research is poultry slaughterhouses that have implemented SNI halal standards and have not implemented SNI halal standards. The study used 52 samples using 2 technic, field studies consisting of observation, interview, questionnaire, documentation, and literature study techniques. Assessment of respondents' knowledge using the order of assessment (Likert scale). The knowledge of workers in an SNI halal standards poultry slaughterhouse regarding commitment and responsibility was in the very high category. However, poultry slaughterhouses do non-SNI halal standards have a very low category. Keywords: poultry slaughterhouses, knowledge, halal